Gaps in EU anti-counterfeit policy and analysis of other measures to prevent the sale of counterfeit goods - Hodaņenoka, Anastasija (Riga Graduate School of Law, 2023)
In 2019 the annual income from the trade in counterfeit goods around the world was approximately USD 509 billion, where EUR 121 billion (6.8% of EU imports) come from the European area.1 Since 2020 to the spread of Covid-19 the growth in e-commerce has become a major driver of the further growth in the counterfeit trade. Digital platforms have simplified the buying and selling process for the third-party sellers to create accounts in a weakly regulated online marketplace environment. While providing significant loss to the uncollected tax revenues of the European economies, the lack of sufficient research conducted in the field of regulation of the sale of counterfeit products highlights the relevance of this study. The study examines the main methods of combating counterfeit products in the EU and assesses the current regulation and proposals for possible innovations that will help to combat the sale of counterfeit products more effectively. The study also analyses the impact of counterfeit products on the economy of the European Union. The study shows the current stage of development and effectiveness of legislations and the need of supplementation and improvement, as well as points out shortcomings. The study recommends the formulation of precise and strong laws, as well as improved public awareness on this issue.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; counterfeit; Research Subject Categories::LAW/JURISPRUDENCE::Private law::Intellectual property law; e-commerce